Strategi Pendampingan Inovasi Produk Olahan Kopi di Desa Palak Tanah, Muara Enim - Abdul Kholek; Muhammad Izzudin; Alfitri Alfitri; Dyah Hapsari (Institut Pertanian Bogor, 2022)
Coffee is one of the leading commodities in Muara Enim Regency, South Sumatra Province. The coffee commodity is the backbone of the village community's economy, especially in the highlands of South Sumatra. One of them is Palak Tanah Village, Muara Enim Regency. The coffee commodity has been processed by farmers from generation to generation with an economic chain that still relies on tokeh (local collectors). Selling coffee beans that are still raw and unprocessed has no added value to the community's economic well-being. This condition because the rural community does not undertake product innovation for coffee commodities. Regarding this circumstance, our team tries to serve and empower through Coffee Processed Product Innovation Assistance in Tanah Palak Village, Muara Enim, South Sumatra. The aim of the assistance from the university is to encourage the successful realization of one product innovation per village for the village community. The method used was PLA (Participatory Learning and Action), divided into two stages involvement in initial mapping and mentoring activities to produce village innovation products. This empowerment activity was carried out for 40 days by Sriwijaya University students and lecture. The main products of this assistance were processed village superior coffee. There are dodol (taffy made) and kemplang (crisp) coffee. The empowerment was done by a team in Palak Tanah Village for 40 days and evaluating whether the village community was able to understand and apply innovations for processed coffee products. The key to the success of this empowerment program is repackaging, branding, and online marketing. In the last week's evaluation, the companion team made sure that the village community was able to market their own products through the online shop.